2006
DOI: 10.1073/pnas.0505123103
|View full text |Cite
|
Sign up to set email alerts
|

TEX14 is essential for intercellular bridges and fertility in male mice

Abstract: Cytokinesis in somatic cells concludes with the formation of a midbody, which is abscised to form individual daughter cells. In contrast, germ cell cytokinesis results in a permanent intercellular bridge connecting the daughter cells through a large cytoplasmic channel. During spermatogenesis, proposed roles for the intercellular bridge include germ cell communication, synchronization, and chromosome dosage compensation in haploid cells. Although several essential components of the midbody have recently been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
276
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(296 citation statements)
references
References 52 publications
10
276
0
4
Order By: Relevance
“…2b). Immunostaining with an antibody against TEX14, a novel protein that localizes to germ cell intercellular bridges and is indispensable for the formation of the bridges [16], showed that similar to those of wild-type mice, the bridges of Nobox −/− mice contain TEX14 protein (Fig. 2e).…”
Section: Nobox +/− Ovariesmentioning
confidence: 97%
“…2b). Immunostaining with an antibody against TEX14, a novel protein that localizes to germ cell intercellular bridges and is indispensable for the formation of the bridges [16], showed that similar to those of wild-type mice, the bridges of Nobox −/− mice contain TEX14 protein (Fig. 2e).…”
Section: Nobox +/− Ovariesmentioning
confidence: 97%
“…In addition, at least Mtap2, Eif4g3, Usp2, Mtap7, Ace, and Tex14 are known to play a role in male fertility (29)(30)(31)(32)(33)(34), and overexpression of Spata17 and Rpgr leads to male infertility (35,36). Therefore, the infertility in the Mrg15 cKO mice could be secondary to alterations in the levels of these proteins.…”
Section: Spermatogenesis In Mrg15mentioning
confidence: 99%
“…Therefore, the infertility in the Mrg15 cKO mice could be secondary to alterations in the levels of these proteins. For example, our group has described the essential roles of TEX14 in male fertility and formation of intercellular bridges (34). The lack of TEX14 leads to the loss of intercellular bridges and the failure of proliferation and differentiation of spermatogonia (34,37).…”
Section: Spermatogenesis In Mrg15mentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of Dazl causes arrest of mitotic germ cells in an inbred genetic background (Lin & Page 2005). Tex14 is required for formation of intercellular bridges of germ cells including spermatogonia (Greenbaum et al 2006). Therefore, these three genes (Mvh, Dazl, and Tex14) function in both the mitotic and meiotic phases of germ cell development, which might also be the case for other genes in Table 1.…”
Section: An Abundance Of Meiosis Factorsmentioning
confidence: 99%